Greening minds before businesses: navigating SDGs hurdles for micro and small hotels in Saudi Arabia - Abu Elnasr E. Sobaih; Ahmed H. Abdou; Hareth Z. Alshamayleh; Ali Saleh Alshebami; Ahmed E. Abu Elnasr (Cogent Business & Management)
This study explores the challenges that face micro and small hotels (MSHs) in their green transformation and meeting the UNSDGs. It explores strategies that should be undertaken by MSHs to mitigate such challenges and align their practices with UNSDGs. To achieve this purpose, a phenomenological research approach was adopted with an interpretive research paradigm using in-depth interviews were undertaken with 42 owners/managers of MSHs in Saudi Arabia. The findings of thematic data indicated several challenges that are categorized broadly under external challenges, resources and owners/managers’ perceptions and attitudes. Challenges are associated with each other and have many sub-associated challenges. These sub-challenges are connected to owners/managers’ erroneous assumptions about green transformation that require high financial capital and resources. They believe that their businesses have no or limited negative impact on the environment. The research stresses the need for greening owners/managers’ minds first to ensure successful green transformation of businesses.